Relationship between self-esteem, body image and well-being and achievement in school: A comparison between single-sex and mixed-sex classes. - Hildur Harðardóttir 1989- (2015)
Many studies have been published about self-esteem, body image and well-being and what affect it has on achievement in school. Also, single-sex classes and mixed-sex classes have been widely studied. Research has indicated that class grades are consistently higher in single-sex classes than mixed-sex classes and that girls are more confident in single-sex classes compare to girls in mixed-sex classes. The main purpose of the current study was to investigate the relationship between self-esteem, body image and well-being and grades in Icelandic and mathematics among children in single-sex classes compared to children in mixed-sex classes. Also, it was hypothesized that 1) girls in single-sex classes have higher self-esteem than girls in mixed-sex classes and 2) girls in single-sex classes show a better academic achievement than girls in mixed-classes. Data from the Icelandic Centre for Social Research and Analysis were used in present study and the sample includes students in fifth, sixth and seventh grade, aged 10-12 years in Icelandic elementary school (n = 2031). The results showed that there was most association between these self-esteem, well-being and body image and grades in Iceland and mathematics among boys in single-sex classes. However, the hypotheses were not supported. Key words: self-esteem, body image, well-being, academic achievement, single-sex classes, mixed-sex classes. Margar rannsóknir um áhrif sjálfstrausts, líkamsímyndar og vellíðan á árangur í skóla hafa verið birtar. Einnig hafa rannsóknir á skólum með kynjaskiptum bekkjum og blönduðum bekkjum verið rannsakað í langan tíma. Rannsóknir hafa gefið til kynna að einkunnir séu ítrekað hærri hjá börnum í kynjaskiptum bekkjum heldur en hjá börnum í blönduðum bekkjum og að stelpur séu öruggari með sig í kynjaskiptum bekkjum heldur en stelpur í blönduðum bekkjum. Megin tilgangurinn í þessari rannsókn var að kanna tengsl á milli sjálftraust, líkamsímyndar og vellíðan og einkunna í stærðfræði og Íslensku hjá börnum í kynjaskiptum bekkjum í ...